Assessment of the economic impact of the meetings industry on the city of Krakow - Borodako, Krzysztof; Seweryn, Renata; Berbeka, Jadwiga; Niemczyk, Agata; Davidson, Rob; Jakóbik, Krzysztof (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The academic world has long endeavoured to make a meaningful contribution to the challenge of measuring the economic impacts of meetings. Existing reviews of the business tourism literature demonstrate that the economic impact of events and meetings is among the crucial themes that have emerged as key research topics in academia. The main aim of the research was an assessment of the impact of the meetings industry on the economy of Krakow. The results are expressed as overall values – comprising direct, indirect and induced effects. The study has used a thorough literature review to identify the best methodology for calculating the impact on the city level. The project consisted in the pilot study and afterwards the main survey method (five different questionnaires were used) which enabled the gathering of the empirical data necessary for the analysis of the economic impact of Krakow’s meetings industry. The calculated input of the meetings industry to the city’s economy is significant, considering how complex Krakow’s economy is. This was the first assessment of the significance of the meetings industry for a city in Central Europe
Argumenta Oeconomica, 2019, Nr 2 (43), s. 191-211
Keywords: economic impact; meetings industry; business tourism; multiplier